The Early Development of Islamic Fiqh in Kufah with Special Reference to the Works of Abu Yusuf and Shaybani (Chapter-2) - Ansari, Zafar Ishaq (Islamic Studies, 2016)
Islamic legal doctrines were formulated as a result of the desire to define and elaborate the religious ethic of the Muslim community. This was naturally done with reference to the teachings of the Prophet. Hence, Islamic law has had a religious character from the beginning and retained this character throughout the centuries. With the emergence of specialists in law, Islamic legal thinking increasingly turned towards formalism. From the vantage point of the classical Islamic fiqh, in respect of legal theory as well as technical legal reasoning the Kufians outpaced other contemporary schools, and anticipated and paved the way for Shafi‘i on several important questions. The Kufians, therefore, represent the indispensable historical link between the ancient schools and Shafi‘i, a link without which the early development of Islamic law cannot be fully appreciated.